Analisis Batasan Usia Capres: Antara Demokrasi, Meritokrasi, Dan Dinamika Politik Indonesia - Hikam Firmansyah; Rio Akbar Ahmad Pratama; Fadlan Nur Azizil; Zhafif Hylni Yulianto (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
The debate on the age limit for presidential and vice-presidential candidates is an important issue in the context of Indonesian democracy. Democracy emphasizes the principles of equality and participation, while meritocracy emphasizes competence and experience. Currently, the minimum age limit for presidential candidates in Indonesia is 35 years old. Debates have arisen over the relevance of this age in the current political context, with arguments in favor of the role of younger generations bringing innovation versus the need for experience and wisdom. This study aims to re-evaluate the age limit for presidential candidates in Indonesia from historical, constitutional and international comparative perspectives, and examine its impact on political dynamics and leadership quality. The research methodology involves literature analysis and recent case studies. The results are expected to contribute significantly to the discussion on the age limit for presidential candidates and its implications for democracy and meritocracy in Indonesia.